2021
DOI: 10.1039/d1sc03625d
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of core–shell nanoparticles by seed-mediated selective deposition

Abstract: Conventional solvothermal synthesis of core-shell nanoparticles result in that covered with surfactant molecules for size control and stabilization, undermining their practicality as electrocatalysts. Here, we report an electrochemical method for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Several groups, including ours, studied single emulsions (water-in-oil and oil-in-water droplets) via single-entity electrochemistry using redox species (e.g., ferrocene and ferrocyanide) contained beforehand [ 23 , 24 , 25 , 26 ]. Furthermore, the electrochemical synthesis of metal particles using a single aqueous droplet has been extensively developed along with the conventional electrodeposition method [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups, including ours, studied single emulsions (water-in-oil and oil-in-water droplets) via single-entity electrochemistry using redox species (e.g., ferrocene and ferrocyanide) contained beforehand [ 23 , 24 , 25 , 26 ]. Furthermore, the electrochemical synthesis of metal particles using a single aqueous droplet has been extensively developed along with the conventional electrodeposition method [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] Recent investigations into the utility of emulsion electrochemistry pioneered nanomaterial synthesis on electrodes. [22][23][24][25][26][27] An emulsion colliding on an electrode serves simultaneously as a reactor and as a template, typically yielding surfactant-free nanoparticles with designed sizes and compositions. [22][23][24]27 A number of research groups have successfully synthesized various types of nanomaterials (metals, 22 oxides, 23 and polymers 25 ) via utilizing the discrete singleentity electrochemistry of normal and reverse emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional electrochemical synthetic approaches thus far, which rely on diffusion and stochastic collisions between emulsions and substrate electrodes, suffer from slow synthesis rates, typically requiring in excess of hours to produce one electrode decorated with an appreciable amount of catalyst nanomaterial. 26 To circumvent these problems, we turned our attention toward Pickering emulsions (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Electrons flow from the anode to the cathode, where metal ions are reduced to form metal NPs. 8,[10][11][12][13][14][15][16][17][18] As an alternative to metal salts as precursors, Reetz et al showed that a Pd sheet could be electrochemically stripped and then ions reduced at a Pt sheet to form Pd NPs. However, the method was only capable of synthesizing NPs less than 5 nm in diameter, with little structural control demonstrated.…”
Section: Introductionmentioning
confidence: 99%